GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 295899 species occurrences available in GBIF matching the query: TaxonKey: Lycopodiaceae. The dataset includes 295899 records from 637 constituent datasets: 5 records from Bioimages. 6 records from National Biodiversity Data Bank. Observation records, 1900-2014. 4 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 1262 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 10 records from Guadeloupe_Herbier. 56 records from JOI - Herbário Joinvillea. 288 records from University of Calgary Herbarium. 647 records from OEH Atlas of NSW Wildlife. 7 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 11 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 1616 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 22 records from HUEM - Herbário da Universidade Estadual de Maringá. 105 records from HUFU - Herbarium Uberlandense. 5666 records from Phanerogamic Botanical Collections (S). 510 records from Jordal. 135 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from Herbier G. Garapin (BOUM). 153 records from University of Vienna, Institute for Botany - Herbarium WU. 22 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 18 records from UFG - Herbário da Universidade Federal de Goiás. 2 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 59 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 16 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 13 records from Census of the flora of Benin. 5 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1324 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 17 records from Online Atlas of vascular plants 2012-2020. 12 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 75 records from IAC - Herbário do Instituto Agronômico de Campinas. 127 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 5 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 178 records from Herbarium WRSL, Flora of the Silesia. 12006 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 8 records from PlutoF platform observations. 43 records from SPSF - Herbário Dom Bento José Pickel. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1078 records from PRECIS. 1985 records from Herbario Nacional Colombiano (COL). 176 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 1 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 1 records from UTEP Plants (Arctos). 258 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 2 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 20 records from SPF - Herbário da Universidade de São Paulo. 112 records from SANT Herbarium vascular plants collection. 153 records from Species plots from the Norwegian Vegetation Mapping Programme. 132 records from UFP - Herbário UFP - Geraldo Mariz. 26 records from University of Amsterdam (NL) - Páramo pollen reference collection. 21 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 256 records from Colección Herbario Federico Medem Bogotá - FMB. 274 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 1 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 791 records from FLORIVON. 497 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 4 records from API_CRSN_Data. 2 records from HERBAM - Herbário da Amazônia Meridional. 70 records from Herbario Pontificia Universidad Javeriana. 328 records from ICN - Herbário do Instituto de Ciências Naturais. 15 records from IICT Herbário LISC. 863 records from Karplanter i vernet barskog og edelløvskog. 700 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 143 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 150 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 22 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 6 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1192 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 5 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 1209 records from The digitization of plant specimens of NTU. 70 records from SA Flora (BDBSA). 120 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 13 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 442 records from Phytochorologie des départements français. 17 records from SMDB - Santa Maria Departamento de Biologia. 128 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 210 records from BioFokus. 158 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 7 records from Colección Herbario Universidad Católica de Oriente. 4925 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 640 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 49 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 451 records from CESJ - Herbário Leopoldo Krieger. 92 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 3 records from HAMAB - Herbário Amapaense. 1002 records from Plantae of Costa Rica (INBio). 88 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 24338 records from Artdata. 10 records from Herbier du Bénin. 5 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 9 records from Flora of Słowiński National Park, Poland. 47 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 3 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb).. 656 records from MBM - Herbário do Museu Botânico Municipal. 19 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase I (Tenango de Doria y Tlanchinol). 135 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 112 records from Stabbetorp - Floristiske registreringer 2016. 1 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 91 records from Herbario Museo de La Salle Bogotá (MLS). 13 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 3 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 109 records from Endemic plants of the Congo basin. 2 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 6 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 183 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 65 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 555 records from OHN. 1494 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 3292 records from Données ONF Faune-Flore-Fonge. 11 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 35 records from FCAB - Herbário Friburguense. 71 records from Herbier de Nouvelle-Calédonie. 34 records from Tallinn Botanic Garden. 21 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 31 records from Herbarium areqvipense (HUSA). 3 records from NCSM PaleoBotany Collection. 15 records from Plant observations from Białowieża National Park. 14 records from Norwegian Biodiversity Information Centre - Other datasets. 8 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 4 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 6 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 5 records from BRFC Black Rock Forest Consortium Herbarium. 13 records from Herbarium of the Université Libre de Bruxelles. 5252 records from Australia's Virtual Herbarium. 710 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 41 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 43 records from Herbier de Strasbourg. 38 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1105 records from Vascular Plant Herbarium, UiB. 47 records from Kathryn Kalmbach Herbarium. 47 records from Natural History Museum Maastricht (NL) - Herbarium. 65 records from Consortium of California Herbaria. 2 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 1339 records from iNaturalist Research-grade Observations. 2 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 34 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 3 records from UCBG TAPIR Provider. 1597 records from CONN. 202 records from HUCS - Herbário da Universidade de Caxias do Sul. 10 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 2 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 36 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 5 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 39 records from University of Lethbridge Herbarium (LEA). 659 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 309 records from Estonian Museum of Natural History. 3 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 10 records from Collection botanique Le Grand A. (BOUM). 120 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 3 records from University of California Museum of Paleontology. 46 records from NINA botanical collection. 26 records from Macrophytes_CLF. 6 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 97 records from ALCB - Herbário Alexandre Leal Costa. 20 records from HUSC - Herbário Unisanta. 2002 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 2 records from HPBR - Herbário Padre Balduino Rambo. 455 records from Estonian University of Life Sciences. 498 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 292 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 40 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 302 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 298 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 2 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 1 records from Waldhusener Moor (Lübeck-Kücknitz). 2 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 1 records from Ortelsbruch - Hangmoor bei Morbach. 5 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 12 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 1 records from Urwald 3 (Bad Waldsee). 2 records from Klütwald. 1 records from Nachtaktiv im Ökogarten (Bad Waldsee). 12 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Bannwald Burghauser Forst. 1 records from Fürstenberger Ralley Teil 3. 115 records from NX - Herbário Nova Xavantina. 6864 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 3 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 13 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 386 records from Base de datos de las pteridofitas del estado de Veracruz, México. 4 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 2107 records from OAC-BIO Herbarium. 1 records from VIC - Herbário da Universidade Federal de Viçosa. 19 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 20 records from Herbario de la Universidad de Granada: GDA. 443 records from naturgucker. 4 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 29 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 30 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 3 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Actuopalynology National Collection (BAPa).. 1 records from The Distribution Atlas of Butterflies in Poland. 11 records from Scottish Natural Heritage - Standing Waters Database. 151 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 18 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 3 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 2 records from Schatzinsel Norderney. 2 records from Naturschutzgebiet Lüneburger Heide. 27 records from Plant specimens of Natural History Museum, Kishiwada City. 66 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 6 records from Plant Specimens collections of the Kyushu UNniversity Museum. 2 records from MfN - Fossil plants (Mesophytic). 22 records from MfN - Fossil plants (Paleophytic). 14 records from Vascular Plants Collection of National Museum of Nature and Science. 1519 records from Dutch Vegetation Database (LVD). 3 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 187 records from Flora Atlas N.T.. 9943 records from INPN - Données flore des CBN agrégées par la FCBN. 25 records from Herbier de Wallis et Futuna. 20 records from EFC - Herbário Escola de Florestas Curitiba. 15 records from ASE - Herbário da Universidade Federal de Sergipe. 225 records from UEC - Herbário da Universidade Estadual de Campinas. 3 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 8097 records from NZ National Vegetation Survey occurrence data. 47 records from FUEL - Herbário da Universidade Estadual de Londrina. 1310 records from ICN - Universidad Nacional de Colombia. 302 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 27 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 380 records from Vascular plant specimens of Akita Prefectural Museum. 14 records from Jardin botanique de Montréal (JBM). 1 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 6 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 137 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 62 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 4 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 4 records from Plant (KOBG_PL). 32 records from Plant (JNHM-PL). 1 records from Plant (SMNH-PL). 2 records from Plant (NHMC-PL). 78 records from Plant (NSMK-PL). 4 records from Plant (JJHA-PL). 9 records from Herbaria of the University and ETH Zürich. 128 records from svalbardflora.no. 62 records from Tiroler Landesmuseum Ferdinandeum. 3 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 534 records from IBF Monitoring of Vascular Plants. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 5 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 3 records from Vascular plant specimens of Iida City Museum. 9278 records from Tropicos Specimen Data. 7 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 2 records from Naturhistorisches Museum Mainz, Botanical Collection. 30 records from Botanical Research Intitute of Texas. 2900 records from Natural History Museum (London) Collection Specimens. 72 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 362 records from Natural History Museum, Vienna - Herbarium W. 2 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 6 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 2 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 4 records from Pteridoflora de Morelos. 2 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 1939 records from NatureServe Network Species Occurrence Data. 6 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 7 records from Flora-On: occurrence data of the flora of mainland Portugal. 2 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 2 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 84 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 10 records from Ireland's BioBlitz. 197 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 2 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 13 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 2 records from Florística de áreas protegidas en el estado de Durango. 2 records from Base de datos sobre la flora de Durango. 8 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 2 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1 records from Plant Specimens of Oiso Municipal Museum. 12 records from Plant specimens of Hokkaido University Museum. 37 records from Pteridophyta specimens of Iwate Prefectural Museum. 575 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 1 records from KNWR Herbarium Collection. 145 records from Dataflos. 244 records from Ibaraki Nature Museum, Vascular Plants collection. 12 records from Tartu University, palaeontology collections. 70 records from Leiner-Herbar Konstanz. 12197 records from NMNH Extant Specimen and Observation Records. 12 records from Universität Salzburg. 35 records from The Himalayan Uplands Plant database (HUP Version 1). 23 records from Andes to Amazon Biodiversity Program. 1 records from Botanical Garden Collection. 36 records from ANTARCTIC PLANT DATABASE. 6 records from Australian Antarctic Division Herbarium. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 1 records from Korean Ethnobotany Database. 771 records from Canadian Museum of Nature Herbarium. 768 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 118 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 34 records from Herbario UNAP. 1000 records from The AAU Herbarium Database. 270 records from Herbarium (ICEL). 157 records from Herbarium (AMNH). 683 records from Observational database of Icelandic plants. 122 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 92 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 755 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 40 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 35 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 29 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 111 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 52 records from Aranzadi Zientzi Elkartea. 1 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 2 records from Universitat de Girona: HGI-Cormophyta. 16 records from CIBIO, Alicante:ABH-GBIF. 14 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 8 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 5 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 40 records from Herbario de la Universidad de Sevilla. 13 records from Herbario de la Universidad de Sevilla, SEV-Historico. 10 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 2 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 210 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 160 records from CUBA:Herbario del Jardín Botánico Nacional, La Habana, Cuba: HAJB-Pteridophyta. 13 records from Institut Botanic de Barcelona, BC. 1205 records from Auckland Museum Botany Collection. 3 records from Botanic Garden of the Finnish Museum of Natural History. 1 records from Kystfuruskoger 2015. 330 records from Herbarium of Jyväskylä University Museum. 8 records from Plant in Baekdu Mountain (KIDR-PL). 9 records from Royal Botanical Gardens Herbarium. 14 records from DAO Herbarium Type Specimens. 12 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 196 records from Paleobiology Database. 1051 records from herbario. 1 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 1 records from Vascular Plants Collection of National Museum of Nature and Science. 451 records from Plant Specimens of Kurashiki Museum of Natural History. 83 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 211 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 121 records from Vascular Plant Collection. 2 records from IIAPPoa. 26 records from Arizona State University Vascular Plant Herbarium. 14 records from Botany registration database by Danish botanists. 194 records from Herbarium Faeroense. 14 records from Botanical Museum, Copenhagen. Database of type specimens. 9 records from Botanical Museum, Denmark. Database of registrations of red listed plants. 90 records from DAV UC Davis Center for Plant Diversity. 202 records from Herbarium (UNA). 3 records from MEXU/Plantas Vasculares. 3 records from MEXU/Tipos de plantas vasculares. 14 records from MEXU/Herbario Los Tuxtlas. 291 records from Actualización de las bases de datos del Herbario XAL. Fase III. 721 records from Plants of Papua New Guinea. 8 records from Flora exsiccata Bavarica. 416 records from Herbarium Berolinense. 35 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 830 records from Observations du Conservatoire botanique national du Bassin parisien.. 134 records from Biologiezentrum Linz. 217 records from Herbarium Senckenbergianum Görlitz (GLM). 1 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 1 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 182 records from USU-UTC Specimen Database. 17 records from Institut Botanic de Barcelona, BC-Histórico. 8 records from Herbarium de Geo. B. Hinton, México. 73 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 1 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 14 records from Plant Specimens of Lake Biwa Museum. 75 records from Vascular Plants Collection of Sagamihara City Museum. 1181 records from Harvard University Herbaria. 42 records from Vascular plants of south-central China. 60 records from Specimen Database of Colorado Vascular Plants. 23 records from Herbarium BSG Vascular Plants. 107 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from EURISCO, The European Genetic Resources Search Catalogue. 90 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 13 records from CVRD - Herbário da Reserva Natural Vale. 825 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 348 records from Kochi Prefectural Makino Botanical Garden. 53 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 103 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 5 records from MEXU/Colección Histórica. 3 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 5 records from Staffordshire Ecological Record - SER Site-based Surveys. 2 records from English Nature Berkshire SSSI Records. 41 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 4 records from Herbario de la Universidad de Arizona, EUA. 15 records from Vascular Plants, Observations, Oslo (O). 84 records from Programa de repatriación de datos de ejemplares mexicanos. 7 records from Oklahoma Vascular Plants Database Provider. 120 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Danielsberg (Mölltal, Kärnten). 7 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Naturschutzstation Schmidsfelden. 2 records from Schlern - (Bozen). 2 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Schule Sulzbach (Oberegg). 2 records from NSG Karwendel. 1 records from Cuxhavener Küstenheiden. 1 records from Promberg1. 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 5 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 1 records from Himmelmoor. 658 records from USF Herbarium. 1796 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 554 records from Atlas Flora Danica. 192 records from Herbarium of Namur. 380 records from Natural History Museum, University of Tartu. 479 records from Herbarium of Umeå University (UME). 8 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 265 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 46 records from Field Museum of Natural History (Botany) Seed Plant Collection. 88 records from MBML-Herbario - Herbário Mello Leitão. 697 records from MPM Milwaukee Public Museum Herbarium. 10 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 150 records from Belgian IFBL Flora Checklists (1939-1971). 63 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 5 records from Spécimens d'herbiers de G. Fenoul (FEN). 17 records from Colorado State University Herbarium. 197 records from EKY_Darwincore. 116 records from MISS_DC_01MAR2006. 96 records from FernsDarwinCore. 57 records from R. L. McGregor Herbarium Vascular Plants Collection. 5 records from EDIT - ATBI in Gemer area (Slovakia). 4 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 11 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 527 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 167 records from Gunma Museum of Natural History, Vascular Plant Specimen. 2 records from Artenvielfalt am Schlern. 3 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1192 records from Plant. 64 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 2 records from Jardín Botánico Atlántico, Gijón: JBAG. 42 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 147 records from Biological and palaeontological collection and observation data MNHNL. 1330 records from Botany Division, Yale Peabody Museum. 37 records from Paleobotany Division, Yale Peabody Museum. 4 records from Collection Pisces SMF. 5 records from HUTO - Herbário da Universidade de Tocantins. 1 records from Collection Mikropaläobotanik SMB. 274 records from Herbarium Senckenbergianum (FR). 10 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 645 records from Database of Native Plants in Taiwan. 2 records from Bryophyte Collection - University of Washington Herbarium (WTU). 1 records from Mycological Collection - University of Washington Herbarium (WTU). 94 records from University of Ghana - Ghana Herbarium. 2 records from Plant of Folklore (KIDR-PL). 1215 records from Herbarium of Taiwan Forestry Research Institute. 9 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 27 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 126 records from Herbario Amazónico Colombiano. 8 records from Plants from India in the vascular plant herbarium, Natural History Museum at the University of Oslo (NHM-UiO). 5 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 20 records from Vegetation data from phytosociological studies of the forests on the Fosen peninsula. 3 records from Plantas Acuáticas de la Orinoquía Colombiana. 34 records from Banco de datos florísticos del Herbario CHAP. 441 records from Precis Plant Data. 2 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 8 records from WII Herbarium Dataset. 172 records from National vegetation diversity inventory and mapping plan. 91 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 386 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 8 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 67 records from Vascular Herbarium, NMBU. 758 records from Wetland Inventory (NV). 64 records from Integración de bases de datos, actualización y sistematización de la colección de flora del Herbario Eizi Matuda (HEM). 171 records from KTU Pteridophyta. 295 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 501 records from UPCB - Herbário do Departamento de Botânica. 16 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 10 records from Faun. 138 records from Bosque Mesófilo de Montaña de México. 1 records from Parcela Permanente en el Pantano Martos. 1 records from condoncollection. 28 records from Flora d'Andorra. 3 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 6 records from HURB - Herbário do Recôncavo da Bahia. 422 records from National System of Protected Areas in Poland - Plants. 2 records from Restauración, protección y manejo de ecosistemas del Parque Nacional Pico de Orizaba y su área de influencia, en colaboración con SEMARNAT, CONANP, CONAFOR y PROFEPA. 11 records from University of Amsterdam (NL) - Páramo vegetation research, Santa Marta and Perijá, Colombia. 43 records from ArtenFinder. 2293 records from Lund Botanical Museum (LD). 2 records from Herbario CTES Plantas Vasculares. 9 records from Census of medicinal plants of Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2010 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 9 records from HVAT - Herbário do Vale do Taquari. 30 records from Geographically tagged INSDC sequences. 57 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 2 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 13 records from TEPB - Herbário Graziela Barroso. 99 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 1 records from HTSA - Herbário do Trópico Semiárido. 3 records from Herbarium togoense. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 8329 records from Norwegian Species Observation Service. 6 records from HVASF - Herbário Vale do São Francisco. 288 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 30 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from HST - Herbário Sérgio Tavares. 11 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 62 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 7 records from Colección de Herbario. 265 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 3 records from R-Tipos - Herbário do Museu Nacional - Tipos. 18557 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 2 records from SBT-Living. 1850 records from Bernice P. Bishop Museum. 10 records from Biodiversidad, hábitat y manejo en el Parque Nacional Pico de Tancítaro, Michoacán, México. 384 records from FURB - Herbário Dr. Roberto Miguel Klein. 43 records from Helechos de la jurisdicción de Corantioquia. 333 records from Carnet en Ligne. 34 records from CRI - Herbário Pe. Dr. Raulino Reitz. 8 records from HUEG - Herbário da Universidade Estadual de Goiás. 88 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 153 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 3 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 13 records from Condon Fossil Collection. 88 records from Colección del Herbario PSO de la Universidad de Nariño. 15 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 9 records from UFACPZ - Herbário da Universidade Federal do Acre. 415 records from Royal Botanic Garden Edinburgh Herbarium (E). 28 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 1179 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 19 records from Michigan State University Herbarium Vascular Plants. 5 records from Forster herbarium, Göttingen (GOET). 2070 records from Botany (UPS). 3086 records from Instituto de Ciencias Naturales. 127 records from LNHG Biological Records Dataset. 13 records from CNMT - Herbário Centro Norte Mato Grossense. 3 records from Type herbarium, Göttingen (GOET). 2444 records from National Forest Inventory (SLU). 1146 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 184 records from Herbarium Specimens of Bonin and Ryukyu Islands. 148 records from HAS - Herbário Alarich Rudolf Holger Schultz. 3 records from Inventario Florístico de la Reserva de la Biósfera La Sepultura del Corredor Biológico Sierra Madre del Sur. Fase II. 4 records from University of British Columbia Botanical Garden Collections (UBCBG). 2 records from Vascular plant diversity in forests. 115 records from Estonian Nature Observations Database. 51 records from NMNH Paleobiology Specimen Records. 103 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 4 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 30 records from crsn_data. 62 records from JPB - Herbário Lauro Pires Xavier. 1 records from Ájtte. 18 records from EAC - Herbário Prisco Bezerra. 244 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 40 records from Herbario de la Universidad Industrial de Santander. 18 records from Base de datos computarizada del herbario CIB, Instituto de Investigaciones Biológicas, Universidad Veracruzana. 16 records from R - Herbário do Museu Nacional. 1632 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 7 records from Verneplan Hjerkinn karplanter. 2 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 2 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1277 records from Vascular plant herbarium, Tromsø Museum. 7 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 35 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 1 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 1610 records from Vascular plant herbarium, NTNU University Museum. 3292 records from Données ONF Faune-Flore-FOnge. 90 records from New Zealand Biodiversity Recording Network. 11730 records from Vascular Plants, Field notes, Oslo (O). 1874 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 11 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 34 records from Herbarium Amazonense. 101 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 13 records from Wilson Botanical Garden - Las Cruces Biological Station. 6 records from SLUI - Herbário Rosa Mochel. 5 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 75 records from Ecofact. 249 records from UB - Herbário da Universidade de Brasília. 230 records from Green Plant Herbarium (TRT). 57 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 49 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 4 records from Herbarium - Las Cruces Biological Station. 19 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 12 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 69 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 2 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 1646 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1714 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 355 records from Allan Herbarium (CHR). 23 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 78 records from SysTax - Botanical Gardens. 3 records from Herbarium of University of Białystok - Vascular Plants. 134 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2 records from Herbarium specimens of CBNA (GAP). 124 records from Flore de Franche-Comté. 5 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 8 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 143 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 34 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 25 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 3 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5078 records from Vascular Plant Herbarium, Oslo (O). 12 records from The Bergius Herbarium. 14 records from Occurrences in SinBIOTA. 19 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 62 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 3 records from African Plants - a photo guide. 25 records from Natural History Museum Rotterdam (NL) - Plantae collection. 23972 records from Flora von Deutschland (Phanerogamen). 1 records from Vascular plants of Amrum 2007-2008. 9 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 527 records from E. C. Smith Herbarium (ACAD). 11 records from Propuesta para sistematizar la colección palinológica de polen reciente y fósil del IGLUNAM. 13 records from BUT Friesner Herbarium. 26 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 4 records from HDJF - Herbário Dendrológico Jeanine Felfili. 4 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 73 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 31 records from Herbarium Erlangense. 6 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 3 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 4 records from Herbier Boreal Confluence (BOUM). 1256 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal).. 7 records from Fusión y actualización de las bases de datos del Herbario de la Facultad de Ciencias, UNAM (FCME), Guerrero. 684 records from National Trust for Scotland Species Records. 31 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2809 records from Vascular plant field notes, NTNU University Museum. 75 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from Rare vascular plant species in North-West of Kostroma region, Russia. 177 records from Fundación Miguel Lillo - Colección Criptogámica. 92 records from SysTax - Herbaria. 101 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 3 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 178 records from Geneva Herbarium – General Collection (G). 552 records from Instituto de Botánica Darwinion. 6 records from Nijmegen Natural History Museum (NL) - Herbarium. 2 records from SJRP - Herbário de São José do Rio Preto. 370 records from Herbarium WRSL, Main Collection. 4 records from Flora of the Stołowe Mts.. 311 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 274 records from CAS Botany (BOT). 50 records from Atlas des plantes vasculaires de Lorraine. 7 records from CPAP - Herbário CPAP. 90 records from National Museum of Natural Science. 6 records from Herbarium specimens of Limoges university (LIMO). 41 records from HEPH - Herbário Ezechias Paulo Heringer. 24 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 5 records from MOSS - Herbário Dárdano de Andrade Lima. 23 records from HRCB - Herbário Rioclarense. 474 records from SJRP-Pteridophyta - Herbário de Pteridophyta de São José do Rio Preto. 777 records from PACA-AGP - Herbarium Anchieta. 20 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences